Tourist attractions are no less popular "Barong brutuk dance tradition Trunyan." - A.A. Ayu Ari Andriani (Bali Tourism Journal, 2017)
The island of Bali not only offers the beauty of tourist objects, but the culture and traditions that exist here can be a special attraction. As the culture and traditions of Trunyan villagers, this place is a unique tourist destination, because it is a funeral of people who are placed only under a tree. Also, Trunyan Village has an Ancient art known as Barong Brutuk, even ancient art that already existed before the influx of Hinduism to Bali.